FisioAr I: mobile app developed for respiratory reeducation in pulmonary rehabilitation (Research, Society and Development, 2022)
The objective was to develop a mobile application for respiratory reeducation in Pulmonary Rehabilitation. The application arose from the need to implement part of the RP proposed in the project before the pandemic, but it became independent of the project, without application in humans and was developed as a final product. It is written in the Java programming language, it was developed through the Kodular platform, which is based on the source code of the App Inventor 2 platform and is compatible with the Android operating system. It has a dynamically created interface, with colorful screens and icons for visual stimulation; as well as audio capture so that the app system recognizes the breath noise towards the cell phone sound sensor, as well as warning message boxes and buttons that direct to guidance texts to introduce the user to the game in question. There is legal protection with the copyright of FisioAr I through the Computer Program Registration Certificate (Annex I), provided by the National Institute of Industrial Property and the Patent Office. The software is a tool created to facilitate and teach the user about ventilatory patterns increased in functional training, in daily life and in its treatment, in search of dynamism and metabolic benefits.